Nepali Migrant Workers amid Covid-19 in Major Destination Countries: A Human Security Approach - Bhattarai, Gaurav; Baniya, Jeevan (Tribhuvan University Journal, 2020)
The global outbreak of novel corona virus has exposed a severe crisis and threat in the human security of the thousands of Nepali workers abroad. It has challenged a rather limited conception and understanding of security in the context of Nepali migrant workers and has led to rethink policies and plans about safe, dignified, and managed migration. This article seeks to identify the situations of Nepali migrant workers in major destinations such as the Persian Gulf and Malaysia and discusses the factors that shape a sense of insecurity/security and dignity among them. In this article, first, we argue that Nepali migrant workers have become vulnerable due to the challenges and risks facing them related to infection and deaths, loss of jobs and income, lack of safe and dignified repatriation, no access to essential services including food, accommodation and health, unsafe working and living situation and discrimination and ill-treatments. Second, we highlight that the government of Nepal needs to effectively regenerate and exercise its labour diplomacy to make the destination countries more accountable to their responsibilities towards labour migrants and their human rights, and equally tailor its development policies to create adequate and decent opportunities within the country.